2017
DOI: 10.1021/acsami.7b06152
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Derived Formation of Ni2P–CoP Bimetallic Phosphides with Strong Interfacial Effect toward Electrocatalytic Water Splitting

Abstract: Bimetallic phosphides have attracted research interest for their synergistic effect and superior electrocatalytic activities for electrocatalytic water splitting. Herein, a MOF-derived phosphorization approach was developed to produce NiP-CoP bimetallic phosphides as bifunctional electrocatalysts for both hydrogen and oxygen evolution reactions (HER and OER). NiP-CoP shows superior electrocatalytic activities to both pure NiP and CoP toward HER and OER, revealing a strong synergistic effect. High-resolution tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
186
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(196 citation statements)
references
References 36 publications
(61 reference statements)
5
186
0
Order By: Relevance
“…[65] Sun et al reported a gadolinium-based MOF [Gd 2 (abtc)(H 2 O) (OH) 2 ]·2H 2 O (H 4 abtc = 3,3′,5,5′-azobenzene tetracarboxylic acid) for photocatalytic HER. In this case, benzenedicarboxylic acid is applied as the organic ligand to link Ni and Co atoms.…”
Section: Functionalizable Organic Linkersmentioning
confidence: 99%
See 2 more Smart Citations
“…[65] Sun et al reported a gadolinium-based MOF [Gd 2 (abtc)(H 2 O) (OH) 2 ]·2H 2 O (H 4 abtc = 3,3′,5,5′-azobenzene tetracarboxylic acid) for photocatalytic HER. In this case, benzenedicarboxylic acid is applied as the organic ligand to link Ni and Co atoms.…”
Section: Functionalizable Organic Linkersmentioning
confidence: 99%
“…Apart from ZIF-67, other Co-based MOFs, [67,[118][119][120] ZIF-8, [121] MOF-74, [53,122] Ni 2 (bdc) 2 ted (bdc = 1,4-benzenedicarboxylic acid; ted = triethylenediamine), [123] other Ni-based MOFs [124] and bimetallic MOFs (such as NiZn-MOF (ted as organic linkers), [125] NiFe-MOF (bdc as organic linkers), [126] NiCo-MOF (bdc as organic linkers) [65] ) are demonstrated as effective precursors for the fabrication of various interesting metal compounds and metal/ carbon composites for electrocatalytic water splitting. …”
Section: Overall Water Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Therefore, there is high demandf or an efficient electrocatalyst which can increase the rate of OER at lower overpotential. [8][9][10][11] Amongt he TMOs, cobalt-based spinel oxides have been shown as outstanding OER electrocatalysts. [4,5] However,t heir scarcity,i nferior durability and excessive cost, limit their use in large-scale industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a low cost and high efficient electrocatalyst for hydrogen evolution reaction (HER) is highly desired to decrease the overpotential and improve the electrolysis rate. Although Nobel metal‐based materials (e. g. Pt‐group metals) are the most frequently used HER catalysts due to their low overpotentials and high current densities, the high cost and scarce abundant have limited their widespread application . Recently, non‐noble metal based HER electrocatalysts, such as Mo 2 C, Co,N‐doped CNTs,, α‐MoB 2 and Co 9 S 8 ,, were prepared to address these issues with good HER activites while some of these materials could lose the catalytic activities during HER conditions and cause the detrimental environmental effects.…”
Section: Methodsmentioning
confidence: 99%